Examining ‘The eye of the earth’ the Pan-Pacific idea & the British dominions, c. 1910-1940 - Phillips, SJ (2022)
This thesis examines the emergence and influence of the ‘Pan-Pacific’ idea from the 1910s-1940s. It makes the case that to a diverse demographic globally, it proved a compelling regional geo-paradigm; the institutions it inspired, significant inter-imperial spaces for representatives from the former British Dominions to consider their society’s place in the world and the region’s globality.